A Comprehensive Accountability Framework for Public Administrators. (2nd January 2018) - Christie, Natasha V.
Abstract : In their current state in the public administration literature, the various accountability frameworks build upon another, but are not in a comprehensive form so that practitioners may make use of them. The Comprehensive Accountability Framework (CAF) synthesizes the major components of prominent accountability frameworks in the literature by linking them together to create an actionable system of accountabilities. Doing so creates a more in depth understanding of accountability that acknowledges the respective values of those within an accountability network while at the same time work to create agreed upon accountability system(s) for their interorganizational relationship.